Translational advances in Sturge-Weber syndrome: Key points to consider: Avances traslacionales en el Síndrome Sturge-Weber: Puntos claves a considerar - Medina-Diaz, Fabiana (2026)
Sturge–Weber syndrome illustrates how a cutaneous lesion can anticipate a cerebral and ocular vasculopathy with significant neurocognitive impact. Although it was previously classified among the phakomatoses, it is now better understood as a sporadic somatic neurovasculopathy. Its incidence is low but consistent across population-based studies. Neuroimaging reveals perivascular calcifications, anomalous venous drainage, and atrophy; clinically, seizures, stroke-like episodes, and neurodevelopmental deficits predominate, with a low frequency of tumors.